Exigência energética e relação carboidrato:lipídio para alevinos de piracanjuba (Brycon orbignyanus) - Borba, Maude Regina de [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
Piracanjuba (Brycon orbignyanus) is a migratory fast-growing omnivore fish, which is threatened to extinction in Paraná and Uruguai River basis in Southern Brazil, due to dam building along the rivers and over exploitation of the stocks, among other factors. Therefore, efforts have been made to raise this fish in captivity for stock enhancement or commercial aquaculture. In the present study, two feeding trials were carried out in order to improve understanding about the bioenergetics of this species. In experiment 1, to determine the possible protein-sparing action of dietary lipid, and its effect on growth, lipogenesis and body composition of piracanjuba fingerlings, six purified diets were prepared combining two protein (30 and 32%) and three lipid concentrations (5.5%, 8.8% e 12.1%), in a factorial arrangement. Triplicate groups of eleven fish (11.3 ± 0.1g/fish) were held in 100-L aquaria supplied with recirculating freshwater, and fed to apparent satiation twice daily for 100 days. Fish daily weight gain, (DWG), daily feed consumption (% body weight, DFC), feed conversion ratio (FCR), protein efficiency ratio (PER), apparent net protein retention (ANPR), apparent net energy retention (ANER) and hepatosomatic index (HSI) were not influenced by dietary protein or lipid concentration (P>0.05). However, body composition was directly affected by dietary treatments (P<0.05). An increase in body fat and dry matter was observed as dietary lipid increased, for both dietary protein concentrations tested. The activity of fatty acid sinthetase enzyme was depressed (P<0.05) by increasing dietary fat levels, glucose-6-phosphate dehydrogenase activity did not differ among dietary treatments (P>0.05), and malic enzyme showed some modulation by dietary protein. The results indicated that an increase from 5.5 to 12.1% in the dietary lipid, at a protein concentration of 30 or 32%, promotes body fat accumulation...

A piracanjuba (Brycon orbignyanus) é um peixe migratório, de crescimento rápido e hábito alimentar onívoro, que está sob ameaça de extinção no sul do Brasil, nas bacias formadas pelos rios Uruguai e Paraná, devido a sobre exploração dos estoques e construção de represas, dentre outros fatores. Desta forma, esforços tem sido feitos para a criação deste peixe em cativeiro, seja para fins comerciais ou para o repovoamento do ambiente natural. No presente estudo, visando obter conhecimentos relacionados à bioenergética desta espécie, dois experimentos foram conduzidos. No experimento 1, seis dietas purificadas foram preparadas combinando duas concentrações de proteína bruta (30 e 32% PB) e três de lipídio (5,5%, 8,8% e 12,1%), em esquema fatorial. Este experimento teve como objetivo determinar a possível ação poupadora de proteína pela adição de lipídio na dieta e o seu efeito sobre o crescimento, lipogênese e composição corporal de alevinos de piracanjuba. Grupos de 11 alevinos (11,3 ± 0,1g/peixe) foram estocados em 18 aquários de 100 L abastecidos por um sistema de recirculação de água e alimentados até a saciedade aparente, duas vezes ao dia, durante 100 dias. O ganho em peso diário (GPD), consumo diário em porcentagem do peso corporal (CD), conversão alimentar (CA), taxa de eficiência protéica (TEP), taxa de retenção de proteína (TRP), taxa de retenção de energia (TRE) e índice hepatossomático (IHS) dos alevinos não foram influenciados pela concentração protéica ou lipídica da dieta (P>0,05), entretanto, a composição corporal foi diretamente afetada (P<0,05). Houve aumento no teor de gordura e matéria seca corporal com o aumento do lipídio da dieta, em ambas as concentrações protéicas. A atividade da enzima ácido graxo sintetase foi inibida (P<0,05) pelo aumento da concentração de lipídio da dieta, a atividade da enzima...
Keywords: Peixe; Peixe - Alimentação; Carboidratos; Lipídios; Bioenergética; Proteínas; Fishes